2009
DOI: 10.1124/jpet.109.150730
|View full text |Cite
|
Sign up to set email alerts
|

Gi-Dependent Cell Signaling Responses of the Human P2Y14Receptor in Model Cell Systems

Abstract: Eight G protein-coupled receptors comprise the P2Y receptor family of cell signaling proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
58
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 39 publications
(39 reference statements)
7
58
0
Order By: Relevance
“…The potency (Table 1) and maximal effect (Table 2) of UDP for inhibition of forskolin-stimulated cyclic AMP accumulation were very similar to the potency and maximal effect of UDP-glucose. As was previously observed with UDP-glucose (Fricks et al, 2009), UDP had no effect on cyclic AMP accumulation in P2Y 14 -HEK293 cells in which GPCR-promoted activation of G i was inhibited by preincubation of cells with pertussis toxin (Fig. 1C).…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…The potency (Table 1) and maximal effect (Table 2) of UDP for inhibition of forskolin-stimulated cyclic AMP accumulation were very similar to the potency and maximal effect of UDP-glucose. As was previously observed with UDP-glucose (Fricks et al, 2009), UDP had no effect on cyclic AMP accumulation in P2Y 14 -HEK293 cells in which GPCR-promoted activation of G i was inhibited by preincubation of cells with pertussis toxin (Fig. 1C).…”
Section: Resultssupporting
confidence: 60%
“…However, most studies of P2Y 14 -R-promoted signaling have relied on overexpression of either G␣ 16 or a chimera of G␣ q (G␣ q/i ) that engineers coupling of this G i -coupled receptor to activation of phospholipase C (Chambers et al, 2000;Freeman et al, 2001;Fricks et al, 2008). Using C6 rat glioma cells stably expressing the human P2Y 14 -R, we recently illustrated that adenylyl cyclase activity in both intact cells and isolated membranes was inhibited by UDP-glucose in a concentration-and pertussis toxin-sensitive manner (Fricks et al, 2009). Based on these and similar results obtained with hP2Y 14 -HEK293 cells, we reasoned that cells displaying P2Y 14 -R-promoted inhibition of adenylyl cyclase provide a more physiologically relevant system for quantification of P2Y 14 -R-dependent signaling over an engineered signaling system that depends on overexpression of a G protein that activates phospholipase C. Given our recent observation of activities of UDP at the P2Y 14 -R transiently expressed with an unnatural chimeric G protein, G␣ q/i , in COS-7 cells, we believed it important to quantify the relative actions of UDP and UDP-glucose for promotion of a native cell signaling response in cell lines stably expressing the human P2Y 14 -R.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On a speculative basis, UDP-Nacetylglucosamine and potentially UDP-galactose and UDPglucuronic acid may contribute to P2Y 14 R-dependent lung phenotypes. However, given the low P2Y 14 R agonist potency exhibited by these UDP-sugars, relative to UDP-glucose [13,54], UDP-glucose predictably is the most important autocrine/ paracrine regulator of P2Y 14 R-mediated lung inflammation. Recent studies examining P2Y 14 R-dependent second messenger formation in model cell lines revealed that UDP is a very potent agonist of this receptor [15].…”
Section: Discussionmentioning
confidence: 99%